Capsule Shimming Developments for National Ignition Facility (NIF) Hohlraum Asymmetry Experiments. (17th February 2018) - Rice, N.; Vu, M.; Kong, C.; Mauldin, M.; Tambazidis, A.; Hoppe, M.; Fitzsimmons, P.; Farrell, M.; Clark, D.; Dewald, E.; Smalyuk, V.
Abstract: Capsule drive in National Ignition Facility indirect-drive implosions is generated by X-ray illumination from cylindrical hohlraums. The cylindrical hohlraum geometry is axially symmetric but not spherically symmetric, causing capsule–fuel drive asymmetries. It is hypothesized that fabricating capsules asymmetric in wall thickness (shimmed) may compensate for drive asymmetries and improve implosion symmetry. Simulations suggest that for high-compression implosions, Legendre mode P4 hohlraum flux asymmetries are the most detrimental to implosion performance. General Atomics has developed a diamond-turning method to form a glow discharge polymer capsule outer surface to a Legendre mode P4 profile. The P4 shape requires full capsule surface coverage. As a result, in order to avoid tool-lathe interference, flipping the capsule part way through the machining process is required. This flipping process risks misalignment of the capsule, causing a vertical step feature on the capsule surface. Recent trials have proven this step feature height can be minimized to 0.25 µm.